Fotograficzna enklawa. Nowy Jork i jego mieszkańcy w soczewce aparatu - Sulejewska, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Photographic enclave. New York City and its inhabitants through camera lens The title phrase “photographic enclave” expresses the condition of projects that tell about a city using a photographic medium. The article discusses three audiovisual works that use photos to portray New York and its inhabitants: Smoke by Wayne Wang and Paul Auster, Stefan Nadelman’s Terminal Bar, and the multimedia project One in 8 Million. The works represent a variety of film models (drama, documentary, interactive media), and their authors use the formal and cognitive aspects of photography in a different ways. The aim of the article is to analyze the function of photography for portraying urban communities and to see if this treatment was successful.